The Working Practices and Job Satisfaction of Dental Hygienists in New Zealand - Kathryn M.S. Ayers, MDS; Alison M. Meldrum, MDS; W. Murray Thomson, PhD; (Blackwell Synergy, 2006)
To describe the current working practices and level of job satisfaction of dental hygienists in New Zealand.